Materials for Actively-Bent Structures. Issue 3 (September 2013) - Kotelnikova-Weiler, N.; Douthe, C.; Hernandez, E. Lafuente; Baverel, O.; Gengnagel, C.; Caron, J-F
Active bending structures need materials with specific mechanical properties such as large admissible strain and sufficiently high stiffness to prevent buckling. This paper proposes to investigate the materials that could be used following Ashby's selection method. Then it focuses on the most affordable materials which are glass fibre reinforced polymers (GFRP) and natural fibre reinforced polymers (NFRP). As the initial selection is based on short term characteristics, the long term behaviour of fibre reinforced polymers is then addressed based on recent durability studies which are needed to ensure the performance, reliability and safety of a structure. It is shown that, depending on the loading type (tension, bending, torsion, alone or in combination…) and on the nature of the components (fibres, matrix and interfaces), the material undergoes several phenomena reducing its mechanical performances and potentially leading to its failure. Finally, this knowledge of the materials, which allows for a better understanding of the specific relation between the material and the active bending structures, is used to give a framework for stress limitations and recommendations for further optimisation of reliable structures.